Significantly dominant warm-core eddies: An ecological indicator of the basin-scale low biological production in the Bay of Bengal. (February 2021) - Jyothibabu, R.; Karnan, C.; Arunpandi, N.; Santhi Krishnan, S.; Balachandran, K.K.; Sahu, K.C.
Highlights: The cumulative impact of cold-core and warm-core eddies in the Bay of Bengal (BoB) is presented. Evidenced strikingly higher geographical area for warm cores compared to the cold-core. The basin-scale cumulative impact of eddies in the BoB is negative on phytoplankton biomass production. Overdominance of warm-core eddies is an environmental indication of low biological production. Abstract: This paper introduces the cumulative impact of cyclonic (cold-core) and anticyclonic (warm-core) eddies on the distribution of phytoplankton biomass in the Bay of Bengal (BoB). Estimations of the ocean surface eddy features in the BoB using satellite-derived monthly, seasonal, and multi-year (2012–2016) datasets showed significant dominance of warm-core features over the cold-core ones. Multi-year monthly data of the BoB evidenced strikingly higher geographical area (%) for warm cores (av. 16.5 ± 5.5) compared to the cold-core features (av. 2 ± 1.2). The highest warm-core extent (%) was in May (av. 25.8 ± 1.4), followed by April (av. 22.6 ± 1.4), February (av. 19.5 ± 0.3) and March (av. 18.3 ± 0.9). Contrastingly, a relatively higher extent (%) of cold cores occurred in November (av. 3.9 ± 2.2), October (av. 3.78 ± 2.0), and December (av. 3.5 ± 2.1). The analysis also showed that the extreme oligotrophy of the study domain during the Pre-Monsoon (March-May) was caused by a robust, warm gyre. Upwelling and winter convection, which enhances phytoplankton biomass in the Arabian Sea, are either very weak or absent in the BoB. Similarly, nutrient inputs through river influx into the BoB are insufficient to enhance phytoplankton stock beyond the shelf waters. In this scenario, we showed here that the significantly larger spread of warm-core over the cold-core eddies is a simple ecological indicator of the basin-scale low phytoplankton stock in the BoB.